2022
DOI: 10.3390/app12168210
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically Hydrolysed Common Buckwheat (Fagopyrum esculentum M.) as a Fermentable Source of Oligosaccharides and Sugars

Abstract: Common buckwheat (Fagopyrum esculentum M.) is highly rich in starches and polysaccharides. Nowadays, the use of common buckwheat in brewing processes and functional product development is gaining popularity as it is gluten-free and therefore suitable for those suffering from coeliac disease. Moreover, enzyme-assisted extraction for common buckwheat releases these oligosaccharides as well as bioactive substances, which can be further used for developing new products. This research aims to compare different enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Amylase family enzymes are often used for starch liquefaction and to achieve the desired viscosity. Due to their high amount of oligosaccharides, i.e., fermentable sugars [58], buckwheat-based milk alternatives have promising applications in fermentation and in the production of dairy free yoghurt-type products. Furthermore, due to their nutritional composition and pH, they are a suitable food matrix for incorporation of probiotics.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Amylase family enzymes are often used for starch liquefaction and to achieve the desired viscosity. Due to their high amount of oligosaccharides, i.e., fermentable sugars [58], buckwheat-based milk alternatives have promising applications in fermentation and in the production of dairy free yoghurt-type products. Furthermore, due to their nutritional composition and pH, they are a suitable food matrix for incorporation of probiotics.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…TKG is a traditional symbiotic culture of bacteria and yeast [ 31 ]. It has been used for centuries to produce kefir [ 26 , 32 ] and is currently introduced in various fermented plant-based beverages [ 33 ]. An investigation of grain-based beverages fermented with Tibetan kefir grains conducted by Streimikyte et al in 2022 identified LAB commonly used in yogurt production for growth and possible prebiotic potential.…”
Section: Introductionmentioning
confidence: 99%